Hábitos de vida saludable (prácticas y creencias) y su relación con el rendimiento académico en estudiantes de odontología. (2020)
Objective: to determine the practices and beliefs of healthy lifestyles and their relationship with academic performance in dental students. Method: a descriptive observational cross-sectional study was carried out. It was applied to 94 undergraduate students of the academic dental program of a University, using the Questionnaire of Practices and Beliefs about Lifestyles, validated by Arrivillaga et al 2002, divided into 2 categories: Practices and Beliefs, as well as 6 subcategories that they are evaluated through 116 questions. Results: the sum of the arithmetic techniques of practices and beliefs that identifies the general lifestyle of the students of the dental school is at a "HEALTHY" level with a score of (293.2554). Compared to healthy style practices, the results that stood out were: self-care and medical care diagnosed as "Unhealthy", score of 49.4; "Healthy" eating habits 44.1. Regarding beliefs, the results were: The condition, physical activity and sport diagnosed as "high" score of 15.2; for sleep it was "low" with 18.8. Regarding the academic performance of the students of the faculty, it was found that there is statistical significance: beliefs in the self-care and medical care dimensions (p = 0.044), eating habits (p = 0.043) and consumption of alcohol, tobacco and other drugs (p = 0.004). Conclusions: the practices and beliefs of the healthy lifestyles of dental students are at a "HEALTHY" level, no statistical relationship was found with academic performance.